Epigenetic mechanisms of plasticity and resistance in glioblastoma: therapeutic targets and implications - Amirmahani, Farzaneh; Kumar, Saurav; Muthukrishnan, Sree Deepthi (Frontiers in Epigenetics and Epigenomics, 2025)
Glioblastoma (GBM), a highly aggressive and malignant form of primary adult brain cancer, poses significant therapeutic challenges. Despite our improved understanding of the cellular and molecular mechanisms underlying tumorigenesis and the evolution of GBM, targeted molecular therapies have failed to improve patient survival outcomes. The failure of standard treatments and targeted therapies is mainly attributed to the acquisition of phenotypic plasticity of tumor cells and GBM stem-like cells. Epigenetic modifications and their mediators have emerged as crucial regulators of phenotypic plasticity, influencing tumor heterogeneity, therapy resistance and disease progression. Here, we summarize and provide insights into epigenetic regulation of GBM plasticity and specifically, focus on the roles played by DNA- and histone modifiers and non-coding RNAs in driving phenotypic plasticity and resistance. We also delve into their dynamics in response to standard therapies and the challenges for targeting them to overcome phenotypic plasticity and resistance in GBM.